Gandrung Sewu Festival: The Eroded Image of the Blambangan People's Heroism - Isfironi, Mohammad; Hargo Yuwono, Pujo Semedi; Margana, Sri (MUHARRIK: Jurnal Dakwah dan Sosial, 2022)
Since it was first held in 2012 the Gandrung Sewu Festival has become a favorite in the Banyuwangi Festival event. The popularity of Gandrung Sewu appears not only because this show is aesthetically appealing, but also it holds the stories and desires of the people Banyuwangi. In addition to describing the implementation of the Gandrung Sewu performance which is part of the Banyuwangi Festival event, this paper also aims to reveal the history of the heroism of the Blambangan people which became the background for the emergence of Gandrung and later became an art performance called the Gandrung Sewu Festival. This paper is based on field note from observations of the Gandrung Sewu Festival and in-depth interviews with resource persons who have competence and relevance. The result of the study show that the Gandrung Sewu not only an art performance created from Gandrung which has become one of the icons of Banyuwangi’s arts and culture, but also an image of the herois of the Blambangan people in a war against foreign domination in the past, the heroism of the Bayu war unites returned the people of the Blambangan who were scattered in a new spirit which was marked by the birth of Banyuwangi. The heroism of the Blambangan people, which the people of Banyuwangi continues to love, continues to be eroded in to a variety of purely aesthetic artistic creativity in order to serve the growing demand for the tourism markes, especially in the era of Regent Abdullah Azwar Anas’leadership in 2010-2020. Key Words : Banyuwangi Festival, Blambangan, Heroism Image, Gandrung Sewu Aesthetics